UM SIMPLES SENSOR DE ÓXIDO DE GRAFITE MODIFICADO COM BENTONITA PARA QUANTIFICAÇÃO DE 17β-ESTRADIOL - TRENKEL, Fernanda Adriéli,; RODRIGUES, Lucas Limeira,; FIORUCCI, Antonio Rogerio,; ARRUDA, Gilberto José, (ANAIS DO ENIC, 2023)
-